A green electrochemical method for the synthesis of new N, N′-diphenylbenzene-1, 4-diamine derivatives. Issue 37 (26th March 2015) - Nematollahi, Davood; Mahdinia, Saeideh; Karimi, Peiman; Salehzadeh, Hamid; Kaihani, Sajad
Abstract : A green method for the synthesis of new organosulfur derivatives based on the Michael reaction of electrochemically generated N, N ′-diphenyl- p -quinonediimine with some thiols is described. Abstract : A green method for the synthesis of new organosulfur derivatives of N, N ′-diphenylbenzene-1, 4-diamine (2a–e ) based on the Michael reaction of electrochemically generated N, N ′-diphenyl- p -quinonediimine with 2-mercaptopyridine, 1 H -1, 2, 4-triazole-3-thiol, 1-phenyl-1 H -tetrazole-5-thiol, 2-mercaptobenzoxazole and 2-mercaptobenzothiazole as nucleophiles in a water/ethanol (25/75, v/v) mixture is described. The thioethers (2a–e ) were synthesized in high yields, without toxic reagents and solvents at a carbon electrode using an environmentally friendly method with high atom economy.